UJI SIFAT FISIK TABLET SALUT ENTERIK KALIUM DIKLOFENAK GENERIK DAN GENERIK BERMEREK YANG BEREDAR DI APOTEK KECAMATAN SIAK HULU - Iga Susanti (Jurnal Penelitian Farmasi Indonesia, 2019)
Diclofenac potassium is a non-steroidal anti-inflammatory drug that is widely used and available in the form of generic tablets and branded generics. This study aims to determine the physical properties between generic and generic branded diclofenac enteric coated tablets circulated at the pharmacy in Siak Hulu District. This type of research is experimental with random sample selection and purposive sampling. Tests were carried out on 2 samples of generic enteric diclofenac enteric coated tablets and 1 sample of generic enteric diclofenac enteric coated tablets. Physical quality tests are carried out such as uniformity of size, hardness, friability, endurance, uniformity of weights, and disintegration time. Based on the results of testing all generic and generic branded potassium enteric coated tablets meet the requirements according to Indonesian Pharmacopoeia and other literature.